2001
DOI: 10.1016/s1010-7940(01)00619-4
|View full text |Cite
|
Sign up to set email alerts
|

Airway complications after lung transplantation: a review of 151 anastomoses

Abstract: In our experience, the incidence of airway complications after lung transplantation is 5.3%. The careful surgical technique and organ preservation, the close surveillance of rejection and infection, and early postoperative extubation might play a role in reducing this incidence. Either surgical therapy or bronchoscopic dilation and stenting methods may contribute to resolve these complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
93
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(97 citation statements)
references
References 23 publications
2
93
0
2
Order By: Relevance
“…Unfortunately, in our study we were not able to look up data on reperfusion edema for the whole cohort because of missing chest X-rays necessary to grade primary graft dysfunction conform the new ISHLT classification. In other studies [14,27,28] AC also resulted in longer intubation periods post-operatively. In our study, we also found a longer duration of mechanical ventilation in patients with AC although the difference did not reach statistical significance.…”
Section: Discussionmentioning
confidence: 73%
“…Unfortunately, in our study we were not able to look up data on reperfusion edema for the whole cohort because of missing chest X-rays necessary to grade primary graft dysfunction conform the new ISHLT classification. In other studies [14,27,28] AC also resulted in longer intubation periods post-operatively. In our study, we also found a longer duration of mechanical ventilation in patients with AC although the difference did not reach statistical significance.…”
Section: Discussionmentioning
confidence: 73%
“…Bronchial ischemia is reported to be a significant risk factor for the development of airway complications [9]. The viability of the donor bronchus is initially dependent upon retrograde low-pressure collaterals derived from the pulmonary artery as bronchial arterial circulation is lost during the harvest of the donor lungs [3].…”
Section: Discussionmentioning
confidence: 99%
“…Reflecting these changes, the contemporary rate of anastomotic lesions following LuTx has dropped from 80% before 1983 [15] to 2.6-23.8% [6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Improvements in surgical techniques, immunosuppressive regimen, and postoperative care have resulted in markedly improved clinical outcomes, as airway complication rates have decreased, presently ranging from 5% to 30% with an associated mortality rate of 2%-3% [58][59][60][61][62][63].…”
Section: Bronchial Stenosis Following Lung Transplantation (Lt)mentioning
confidence: 99%